EXAMINING THE PROBLEMS ENCOUNTERED BY SCHOOL ADMINISTRATORS IN ADMINISTRATIVE PROCESSES AND SOLUTION PROPOSALS - AKAY , Mehmet; İPEK, Mehmet Barış (SSD Journal, 2022)
The aim of this research is to determine the problems that school administrators encounter in administrative processes and to make evaluations on the subject by making use of solution suggestions on these problems. 20 school administrators working in official kindergartens, primary schools, secondary schools and high schools in Antalya’s Kepez district participated in this study, which was carried out in a qualitative research method and phenomenology design. 3 of these participants are kindergarten, 8 primary school, 6 secondary school and 3 high school administrators. According to the results of the analysis, the themes of decision, planning, organization, communication, influencing, coordination, evaluation and the competence levels of school administrators in the administrative field were formed within the scope of management processes. According to the results of the research, it is seen that the decision process is shaped based on the legislation, teachers’ participation in the decision is mostly through meetings, parents mostly participate in the decision through parent meetings and parent representatives, and the factors limiting the decision process are mostly reluctance, legislation, economic factors and time constraints. It has been observed that the planning process varies according to the school level, the follow-up of short and long-term plans is carried out by the school administration, and other stakeholders participate through the boards and commissions. It has been seen that the legislation is based on the organization process and attention is paid to the abilities and experience of the people, the communication method is used first in conflict resolution, and legal processes are applied in cases that cannot be resolved in this way. It has been observed that verbal and written communication are used in the communication process, technological methods are used, the prejudices of the managers, personal interests come to the fore, and there are communication problems such as not listening to the other person. It is seen that verbal and written influencing methods are used and authority is distributed in the influencing process. In the coordination process, it was seen that various activities were organized to increase coordination and social values were given importance. In the evaluation process, it is seen that the supervision of the teachers is mostly done through course supervision and subjective evaluation, and the students are evaluated according to the school type and level. Regarding the proficiency levels of school administrators, it is seen that the training received by the administrators before and after the service is not sufficient.